Development and validation of methods of analysis of active substances in emulgel with thick extract of Tanacetum parthenium - Velya, Maria; Ruban, Olena; Ponomarenko, Tetyana; Yevtifieieva, Olha (Annals of Mechnikov's Institute, 2023)
Introduction. It is known that inflammatory diseases of the muscular and skeletal systems are one of the most common pathologies affecting bones, joints, muscles, and connective tissue. These disorders can lead to loss of working capacity, deterioration of the quality of life, and disability. For the treatment of the above-mentioned pathology, soft drugs containing active pharmaceutical ingredients of the NSAIDs group are used. These drugs are not recommended to be used for more than 14 days because with long-term use on large areas of the skin, they can cause systemic side effects. Herbal preparations are practically devoid of these disadvantages, can be used for a long time and do not cause addiction. Therefore, the composition and technology of a soft medicinal product in the form of emulgel with a thick extract of the tanacetum parthenium (TETP) of the Asteraceae family was developed. The range of biologically active substances of the tanacetum parthenium provides high anti-inflammatory, antibacterial and analgesic effects. The objective of this article is to develop methods for determining active pharmaceutical ingredients (APIs) in the emulgel composition. The planning of the study on standardizing the quality of the studied drug included the development of a test for the identification and methods of determining the quantitative content of API; validation studies of methods of quantitative determination in accordance with the requirements of the general article of SPhU (State Pharmacopoeia of Ukraine) 2.4, 5.3.N.2 "Validation of analytical methods and tests". Material & methods. Identification of API in the emulgel for the presence of hydroxycinnamic acids. With the identification purpose, we selected and worked out the unified pharmacopoeial method during the analysis of the studied finished dosage form. The research was carried out by the method of thin-layer chromatography (TLC). The study of the quantitative content of phenolic components in the emulgel was carried out according to the content of the amount of hydroxycinnamic acids and the amount of flavonoids. Quantitative determination of the amount of hydroxycinnamic acids converted to chlorogenic acid. According to the method of SPhU “Nettles leaves", the optical density of the tested solution was measured immediately at a wavelength of 525 nm, using a compensating solution as a comparison solution. Quantification of the amount of flavonoids converted to hyperoside. According to the method given in the monograph of the SPhU "Hawthorn leaves and flowers N", the optical density of the tested solution was measured 30 minutes after preparation at a wavelength of 410 nm. Results & discussion. Based on the results of the study, the most optimal conditions for TLC analysis were determined for the purpose of identifying marker substances of hydroxycinnamic acids shows the sequence of zones on the chromatograms of the comparison solution and the test solution. The chromatogram of the tested solution should show zonic acid and chlorogenic acid. In addition, other zones may also be detected on the chromatogram of the tested solution. It was indicated that the content of the sum of hydroxycinnamic acids converted to chlorogenic acid in the tested emulgel dosage form is within 3.1048±0.75 mg (RSD=0.72%, ɛ=0.92%). Our studies revealed a recovery percentage of 99.48 - 101.32% (100.40% ± 0.92%), which indicates that the developed method was accurate, selective, fast and economical. It was established that the content of flavonoids in terms of hyperoside in the tested emulgel dosage form is within 0.7995±0.29 mg (RSD=0.51%, ɛ=0.68%). Our studies revealed a recovery percentage of 99.58 - 100.60% (100.09% ± 0.51%), indicating that the developed method was accurate, selective, fast and economical. Conclusion. Methods for the identification of APIs in an emulgel based on tanacetum parthenium have been developed. Based on the results of the study, the most optimal conditions for TLC analysis were determined for the purpose of identifying marker substances of hydroxycinnamic acids. A set of methods for quantitative determination of phenolic components in emulgel using spectrophotometry has been developed. When conducting validation studies of the methodology for quantitative determination of the amount of HCA and the amount of flavonoids in the composition of the emulgel, the following metrological characteristics were checked: specificity, linearity, correctness, precision and intra-laboratory precision. Taking into account the regulated requirements for the content of the group of biologically active substances, and the peculiarities of spectrophotometric determination by the method of the specific absorption index, the criteria for the acceptability of the analytical technique were calculated. Key words: emulgel, Tanacetum parthenium, hydroxycinnamic acids, hyperoside.